1992
DOI: 10.1111/j.1365-2761.1992.tb01236.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influencing the prevalence of a cutaneous ulcerative disease (red spot) in the sea mullet, Mugil cephalus L., in the Clarence River, New South Wales, Australia

Abstract: A cutaneous ulcerative disease (red spot) in sea mullet, Mugil cephalus L., from the Clarence River, New South Wales, Australia, was first reported in 1972. In this study, reports of disease outbreaks have been compared with rainfall and river flow records for the period from 1972 to 1988. Detailed disease prevalenee, rainfall, river flow and water quality data were compared for the period from 1985 to 1988. Significant correlations between weekly rainfall in the lower catchment and the prevalence of early sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…This is consistent with most outbreaks of EUS, which tend to be associated with low and declining water temperatures and high rainfall [6], [9], [25], [33]. Virgona [16] reported significant correlation between rainfall and the prevalence of early stage lesions in sea mullet Mugil cephalus (L., 1758), and found that progression to later stage ulcers occurred after the high flows. Outbreaks of EUS in cultured B. bidyanus at the Grafton Aquaculture Centre occur only when water is pumped from the Clarence River during high flows or floods, and when fish in the river are known to have EUS [38].…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with most outbreaks of EUS, which tend to be associated with low and declining water temperatures and high rainfall [6], [9], [25], [33]. Virgona [16] reported significant correlation between rainfall and the prevalence of early stage lesions in sea mullet Mugil cephalus (L., 1758), and found that progression to later stage ulcers occurred after the high flows. Outbreaks of EUS in cultured B. bidyanus at the Grafton Aquaculture Centre occur only when water is pumped from the Clarence River during high flows or floods, and when fish in the river are known to have EUS [38].…”
Section: Discussionsupporting
confidence: 82%
“…Lesions can be induced experimentally only if zoospores or hyphae are injected intramuscularly into fish or if fish with areas of abraded skin are exposed to zoospores (Roberts et al 1993, Callinan et al 1995b). Outbreaks of EUS in estuarine fish in the Richmond River and elsewhere have been associated spatially with tributaries draining ASS areas and temporally with rain events (Virgona 1992, Callinan et al 1993, 1995b, Sammut et al 1995. We suggest that propagules of the causative Aphanomyces sp.…”
Section: Discussionmentioning
confidence: 61%
“…Further predisposing factors that have been suggested to be involved in EUS outbreaks include water quality–associated factors [i.e. drop in water salinity, low alkalinity and high ammonia, generally poor water quality, low oxygen levels (Khan et al., 2001; Virgona, 1992; Mohan et al., 1999; Asoka et al., 1999; Callinan et al., 1989)], exposure to toxins (Dykstra and Kane, 2000) and infection with ectoparasites, bacteria or viruses (Lilley et al., 1998). Most of these factors may lead to or be associated with skin injury, which may be the real predisposing factor.…”
Section: Resultsmentioning
confidence: 99%